Kapitał ludzki - dystans rozwojowy Polski do Unii Europejskiej - Węgrzyn, Grażyna (Human capital - developmental gap between Poland and the EU, 2006)
The article attempts to present the quality of human capital in Poland as compared to the EU15 member slates. Human capital quality is primarily affected by investments in education, knowledge and R&D. Those are the main determiners of the nature of economic growth, in particular the closing of technology and productivity gaps. This in turn promotes catching up with the development level of economically developed countries. The analysis reveals that the general education level of Polish workforce is relatively high, and Polish employees are educated at the level similar to that of the European population. The socio-economic transformations in Poland require continuous educational efforts, particularly in the sphere of permanent education in various organisational forms to suit both the demands oflabour market and the aspirations of people receiving education.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 322-329